Flood Early Detection Using Internet of Things Based on Flood-Ramped Areas - Alfajri, Tommy Rizky; Habibullah; Hastuti; Elvanny Myori, Dwiprima (Department of Electrical Engineering Universitas Negeri Padang, 2024)
Indonesia is a tropical country that experiences very high rainfall. Very heavy rainfall is the reason for flooding. During the rainy season, continuous rain causes the volume of water in the river to increase and has the potential to cause flooding in several areas. Therefore, an early flood detection tool is needed as an alarm to detect and monitor the increase in water volume in the river and as a measure of rainfall that occurs by utilizing Internet of Things technology to make it easier for people to obtain information about the flood alert status in the area. This early flood detection tool method uses the JSN-SR04T sensor which is used to measure the water level in the river, the YL-83 sensor which is used to estimate the rainfall that occurs, Telegram as an Internet of Things media, and Solar panels as Off Grid PLTS. After testing and analyzing the early flood detection tool using ESP8266 based on the Internet of Things in flood-prone areas, the conclusion is that the early flood detection tool works well and the results achieved are in accordance with the function and work of the tool